1994
DOI: 10.1161/01.cir.89.4.1580
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin in human congestive heart failure.

Abstract: BACKGROUND Although recent investigations report the elevation of plasma endothelin (ET) in congestive heart failure (CHF), it remains unclear if this elevation is that of the biologically active peptide ET-1 or of its precursor big-ET. Furthermore, it is unclear if such elevation is associated with increased myocardial ET and if the molecular form from cardiac tissue is altered ET. Last, it remains to be established whether circulating ET is increased at the earliest stage of CHF in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
196
0
11

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 527 publications
(227 citation statements)
references
References 39 publications
20
196
0
11
Order By: Relevance
“…Likewise, plasma endothelin concentration in patients with CHF has been shown to be closely related to pulmonary artery pressure values. 28 In our study, PRA was significantly increased only in class IV patients. Our observations confirm and extend the findings of others who have shown that angiotensin activity is increased only in the more advanced phases of heart disease.…”
Section: American Heart Journalsupporting
confidence: 40%
“…Likewise, plasma endothelin concentration in patients with CHF has been shown to be closely related to pulmonary artery pressure values. 28 In our study, PRA was significantly increased only in class IV patients. Our observations confirm and extend the findings of others who have shown that angiotensin activity is increased only in the more advanced phases of heart disease.…”
Section: American Heart Journalsupporting
confidence: 40%
“…Heart failure is associated with increased circulating vasoconstrictors such as endothelin (ET), 41,42 as well as a reduction in vasodilators such as prostacyclin. 43 ET-1 potently induces slowly developing, long-lasting contractions in the CC and penile vessels, and has been suggested to contribute to the maintenance of corpus cavernosal smooth muscle tone.…”
Section: Endothelin Elevationmentioning
confidence: 99%
“…3,18 An aggravation of pulmonary hypertension during and after CPB, among other reasons, has been explained by CPB induced endothelial dysfunction. 19 A decrease of the basal endothelial NO release has been discussed as one possible explanation.…”
Section: Discussionmentioning
confidence: 99%